Constructing graphene nanostructures with zigzag edge terminations by controllable STM tearing and folding. (15th September 2020) - Shi, Li-Juan; Yang, Li-Zhen; Deng, Jia-Qi; Tong, Ling-Hui; Wu, Qilong; Zhang, Li; Zhang, Lijie; Yin, Long-Jing; Qin, Zhihui
Abstract: Graphene nanostructures with specified edge terminations has attracted considerable attention owing to their unique electronic properties induced by the edges. However, an efficient way to controllably fabricate such nanostructures is still highly desired. Here, we show that graphene nanostructures with zigzag edge terminations can be easily and efficiently constructed at room-temperature by tip manipulation of a scanning tunneling microscope (STM). Though intentionally increasing the tip-graphene interaction, we controllably tear and fold graphene sheets against step edges and successfully fabricate nanoscale graphene islands such as quantum dots and nanoribbon-like structures on graphite. Interestingly, the tearing directions are found to mainly along the zigzag orientations of graphene hexagonal lattice, leading to the generated graphene nanostructures possessing the same specified edges with well zigzag terminations. Theoretical modelling demonstrates that the enhanced tip-graphene repulsive force can account for the tearing and folding processes, whereas the preferential zigzag-tearing is attributed to the predicted lowest bond-breaking energy of the zigzag orientation in graphene. Our experiment provides a simple and controllable method for fabrication of graphene nanostructures with precise zigzag edge terminations. The obtained zigzag-edge-terminated graphene nanostructures also provide a platform for engineering novel quantum properties. Graphical abstract: Image 1 Highlights: Graphene monolayer sheet can be controllable teared by a nanoscale tip. The tearing of graphene is mainly along the zigzag orientation. The teared graphene edge shows a well zigzag termination. STM is an efficient tool for creating graphene nanostructures with zigzag edges.